Miscibility of light oil and flue gas under thermal action - Changfeng XI; Bojun WANG; Fang ZHAO; Daode HUA; Zongyao QI; Tong LIU; Zeqi ZHAO; Junshi TANG; You ZHOU; Hongzhuang WANG (Petroleum Exploration and Development, 2024)
The miscibility of flue gas and different types of light oils is investigated through slender-tube miscible displacement experiment at high temperature and high pressure. Under the conditions of high temperature and high pressure, the miscible displacement of flue gas and light oil is possible. At the same temperature, there is a linear relationship between oil displacement efficiency and pressure. At the same pressure, the oil displacement efficiency increases gently and then rapidly to more than 90% to achieve miscible displacement with the increase of temperature. The rapid increase of oil displacement efficiency is closely related to the process that the light components of oil transit in phase state due to distillation with the rise of temperature. Moreover, at the same pressure, the lighter the oil, the lower the minimum miscibility temperature between flue gas and oil, which allows easier miscibility and ultimately better performance of thermal miscible flooding by air injection. The miscibility between flue gas and light oil at high temperature and high pressure is more typically characterized by phase transition at high temperature in supercritical state, and it is different from the contact extraction miscibility of CO2 under conventional high pressure conditions.